Government Offices, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
Exterior view of government buildings, the Red House - the seat of Parliament in the Republic of Trinidad and Tobago. The architectural style of the Red House is Greek revival. A man is seen riding a bicycle on the road outside the building. Postcard number 25612.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Architecture--Trinidad and Tobago; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Red House, The